Estrogen and estrogen receptor alpha promotes malignancy and osteoblastic tumorigenesis in prostate cancer - Mishra, Sweta (Impact Journals LLC, 2015)
The role of estrogen signaling in regulating prostate tumorigenesis is relatively underexplored. Although, an increasing body of evidence has linked estrogen receptor beta (ERβ) to prostate cancer, the function of estrogen receptor alpha (ERα) in prostate cancer is not very well studied. We have discovered a novel role of ERα in the pathogenesis of prostate tumors. Here, we show that prostate cancer cells express ERα and estrogen induces oncogenic properties in prostate cancer cells through ERα. Importantly, ERα knockdown in the human prostate cancer PacMetUT1 cells as well as pharmacological inhibition of ERα with ICI 182,780 inhibited osteoblastic lesion formation and lung metastasis in vivo. Co-culture of pre-osteoblasts with cancer cells showed a significant induction of osteogenic markers in the pre-osteoblasts, which was attenuated by knockdown of ERα in cancer cells suggesting that estrogen/ERα signaling promotes crosstalk between cancer and osteoblastic progenitors to stimulate osteoblastic tumorigenesis. These results suggest that ERα expression in prostate cancer cells is essential for osteoblastic lesion formation and lung metastasis. Thus, inhibition of ERα signaling in prostate cancer cells may be a novel therapeutic strategy to inhibit the osteoblastic lesion development as well as lung metastasis in patients with advanced prostate cancer.